First insights into past biodiversity of giraffes based on mitochondrial sequences from museum specimens – Corrigendum - Petzold, Alice; Magnant, Anne-Sophie; Edderai, David; Chardonnet, Bertrand; Rigoulet, Jacques; Saint-Jalme, Michel; Hassanin, Alexandre (European Journal of Taxonomy, 2020)
The present corrigendum corrects errors that occurred in: Petzold A., Magnant A.-S., Edderai D., Chardonnet B., Rigoulet J., Saint-Jalme M. & Hassanin A. 2020. First insights into past biodiversity of giraffes based on mitochondrial sequences from museum specimens. European Journal of Taxonomy 703: 1–33. https://doi.org/10.5852/ejt.2020.703